Five in a row—reactions of smokers to tobacco tax increases: population-based cross-sectional studies in Germany 2001–2006. Issue 1 (12th February 2007) - Hanewinkel, Reiner; Isensee, Barbara
Abstract : Objective: To assess reactions of smokers to five waves of tobacco tax increases in Germany. Design: A 10-wave cross-sectional study, with assessments before and after the tax increases. Setting: General population of Germany. Participants and methods: 10 representative samples from the general population with a total number of 27 608 people aged ⩾14 years, including 8548 smokers (31% of the total sample), were interviewed. Outcome measures: Reflection on smoking behaviour, and smoking behaviour (quitting, reducing, switching to a cheaper brand or no change) before and after tobacco tax increases. Results: Before the tax increases, one third to more than half of the smokers reflected on their smoking behaviour, 9.7–13.9% intended to quit, 23.4–34.7% intended to reduce smoking and 10.8–16.4% intended to switch to cheaper tobacco products, whereas 36.1–52.1% did not intend any change at all. After the tax increases, one fourth to more than one third reported to have reflected on their smoking behaviour, 4.0–7.9% quit smoking owing to the increase, 11.5–16.6% reduced consumption and 11.0–19.9% switched to cheaper products. Significant associations were found between the height of the price increase and the intentions and reactions of smokers. Conclusions: Price increases lead to a substantial reflection on smoking and intended and realised behaviour changes such as reduced consumption and switching to cheaper tobacco products. These effects are more pronounced the more the price rises. Therefore, taxation policy will lead to quitting and reducing smoking. However, complementary measures should also be taken to prevent smokers switching to cheaper tobacco products, which would reduce the effectiveness of taxation policy.